Introduction to international law - "Janis, Mark W." (New Delhi, 1989)
Written by leading scholars, each title in the "Introduction to Law" series contains comprehensive treatment in black-letter style. Featuring footnotes citing to case law, statutory and other authorities, these volumes are ideal for in-depth research on particular issues and points of law.
Keywords: International law